Tertiary care centre as safety net of tuberculosis diagnosis in National tuberculosis elimination programme in India - Basavegowdanadoddi Marinaik, Shrinivasa; Selvaraju, Sriram; Srinivasan, R.; ., Krishnamoorthy; Raina, Sunil; Sood, Abhilash; Madhavi, Devi; ., Padmapriyadharsini (International Journal Of Community Medicine And Public Health, 2022)
Background: About one-fifth of the global gap in TB diagnosis was contributed by India which translates to roughly over half a million cases. Meanwhile the National tuberculosis elimination programme has made coordinated efforts to involve public and private health providers in accelerating TB notification. Government medical colleges which are tertiary care centres act as important catchment point for referral as well as for walk-in for tuberculosis diagnosis. The aim of the study was to evaluate the proportion of TB cases notified from various departments of medical colleges to NTEP for TB diagnosis and referral pattern of the presumptive TB patients. Methods: This was a descriptive study. Data were collected of all presumptive TB patients referred from various departments of 4 selected tertiary care centres to NTEP for TB diagnosis between 1January to 31December 2018. Results: A total of 1601 presumptive TB patients were registered in the study period, of whom 67% were microbiologically confirmed TB patients. Overall, 44% of presumptive TB patients were referred from the pulmonary medicine department, with 26%, 15%, and 4% from general medicine, surgery, and integrated counselling and testing centres departments respectively (χ2=1856.647, p<0.000). Conclusions: Our study revealed that the proportion of TB patients notified by the medical colleges was high. Further strengthening of the referral system increases TB case detection thereby enabling early initiation of TB treatment leading.